Work Engagement Guru Generasi Milenial Dan Generasi Z - kusuma, andia; Rachmawati (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Islam Raden Rahmat Malang, 2026)
This study investigates the differences in work engagement between millennial and Generation Z teachers. Work engagement is defined as the emotional commitment an employee has towards their organization and goals. The research involved quantitative methods, using questionnaires distributed to teachers in Malang, Indonesia, to measure their levels of vigor, dedication, and absorption—the three dimensions of work engagement. The results indicated a significant difference in work engagement between the two generations, with millennial teachers exhibiting higher levels of engagement compared to Generation Z teachers. This difference is attributed to millennials' preference for challenges and independence, while Generation Z teachers tend to rely more on technology and may struggle with perseverance in the face of difficulties. The findings suggest the need for tailored approaches to foster work engagement among different generations of teachers to create a more conducive working environment and improve educational outcomes.